Training practices and job performance in public universities: leveraging on self-efficacy and organizational politics - Claudia Omari Somuah; Henry Kofi Mensah; Prince Gyimah (Cogent Business & Management, 2024)
This study examines the effect of training practices on job performance in the public sector of a sub-Saharan African region. Building on social cognitive theory, this study integrates the mediating role of self-efficacy and the moderating role of perceived organizational politics to explain employees' performance in public universities. This study is a quantitative survey using Structural Equation Modeling (SEM) to analyze the responses of 370 non-teaching staff members at public universities in Ghana. The findings show a positive and significant relationship between training and job performance. The study also finds that self-efficacy fully mediates the effect of training on task and contextual performance but partially on adaptive performance. The study further establishes that perceived organizational politics moderate the effect of training on contextual performance but not on self-efficacy and job performance. Again, perceived organizational politics moderated the relationship between self-efficacy and job performance. Based on the findings, this study provides two key practical implications for the leadership of public institutions in general and public universities. First, the human resources divisions of various public universities must concentrate on training to enhance job performance. Second, the directorate of human resources of public universities and all public sector institutions must devise strategies to minimize organizational politics, which negatively affects overall job performance. Implications for theory and practice are also discussed.
Keywords: 650; Organizational politics; self-efficacy; public sector; training and performance; universities; Sub-Saharan Africa